2013
DOI: 10.1136/annrheumdis-2012-eular.2283
|View full text |Cite
|
Sign up to set email alerts
|

THU0318 A prospective comparative study of three methods of assessment of the knee joint in juvenile idiopathic arthritis: Clinical examination, ultrasound and MRI. (a newly developed knee mri scoring system)

Abstract: Background Juvenile Idiopathic Arthritis (JIA) is the main cause of chronic arthritis in children, and it can lead to joint damage and disability. Detecting early articular involvement in JIA is therefore of crucial importance to prevent cartilage and bone damage in these young patients. Since 2004 we have undertaken a prospective study of children with newly diagnosed JIA with knee involvement, and we noted that, not infrequently, knees deemed clinically normal had appreciable effusion on ultrasound (US). Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Only one study on this topic was found in the literature review and was presented in conference abstract form. 36 Additional study is also needed about what size effusion should change clinical management. Previous studies have shown that ultrasound and MRI can detect knee effusions of 1-4 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study on this topic was found in the literature review and was presented in conference abstract form. 36 Additional study is also needed about what size effusion should change clinical management. Previous studies have shown that ultrasound and MRI can detect knee effusions of 1-4 mL.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies compared US with MRI in the detection of inflammation, particularly at the knee 13 14 33 34. These studies have shown MRI to be better in detecting knee inflammation than US (mean detection rate 1.20-fold, range 0.63–1.56-fold) and in particular MRI was better than US in differentiating pannus from effusion 13.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have evaluated the performance of the MSUS against physical examination, laboratory markers of inflammation, or both [33][34][35] as well as agreement between clinical, US, and MRI assessments in the knee joints of children. 36 However, inference of the validity of the MSUS for JIA based on these studies is problematic. These prior studies did not use 1) validated US definitions of synovitis and its elementary components, [37][38][39] nor did they use 2) standardized and reliable acquisition imaging protocols and scoring systems for the MSUS.…”
Section: Discussionmentioning
confidence: 99%
“…In JIA, studies that support the validity of the MSUS as an imaging biomarker are scarce. Prior studies have evaluated the performance of the MSUS against physical examination, laboratory markers of inflammation, or both 33–35 as well as agreement between clinical, US, and MRI assessments in the knee joints of children 36 . However, inference of the validity of the MSUS for JIA based on these studies is problematic.…”
Section: Discussionmentioning
confidence: 99%